2017
DOI: 10.3390/ijms18112241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Late Gestational Fetal Exposure to Dexamethasone Administration on the Postnatal Hypothalamus-Pituitary-Adrenal Axis Response to Hypoglycemia in Pigs

Abstract: Background: Prenatal glucocorticoid administration alters the activity of the fetal hypothalamic-pituitary-adrenocortical axis (HPAA), and correspondingly the adenocorticotropic hormone (ACTH) and cortisol levels after birth. The dosages required for these effects are critically discussed. Activation of the HPAA is related to metabolic syndrome and diabetes mellitus. Hypoglycemia is the classic side effect of antidiabetic treatment. We hypothesized that a low dosage of dexamethasone in late pregnancy alters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…CBF was recorded at a sample rate of 40/s with a laser Doppler flowmeter (DRT4, Moor, Devon, UK). After the experiment animals were euthanized by intravenous injection of pentobarbital sodium (Narcoren, Merial, Halbergmoos, Germany) as described previously [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…CBF was recorded at a sample rate of 40/s with a laser Doppler flowmeter (DRT4, Moor, Devon, UK). After the experiment animals were euthanized by intravenous injection of pentobarbital sodium (Narcoren, Merial, Halbergmoos, Germany) as described previously [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors correlated the dampened stress response of the HPA axis in the presence of their pups in lactating rats to the high levels of circulating prolactin levels and increased prolactin receptor expression in the central nervous system and the restoration of the stress response to pre-pregnancy levels occurred once prolactin and prolactin receptor levels returned to their pre-pregnancy state. The second article by Schiffner et al [ 3 ] hypothesizes that prenatal maternal exposure to low doses of the synthetic glucocorticoid dexamethasone may cause an alteration of the counter regulatory response of endogenous ACTH and cortisol during hypoglycemia. This hypothesis is based on the observations that stress hormones, such as ACTH and cortisol, stimulate gluconeogenesis and glucose release, that the activation of the HPA axis is related to metabolic syndrome and diabetes mellitus, and that hypoglycemia, with a resulting increase in ACTH and cortisol as a counter-regulatory response, is a common side effect of anti-diabetic treatment.…”
Section: The Role Of the Hpa Axis In Pregnancy And Early Developmementioning
confidence: 99%
“…Hypoglycaemia is one of the most common and dangerous side-effects of anti-diabetic treatment. In previous experiments, we were able to demonstrate that exposure to late-term GC causes elevated concentrations of ACTH and cortisol both at baseline and during hypoglycaemia in pigs as compared to control animals [ 25 ]. Moreover, in a different study, we showed that in pigs with unilateral renal denervation, the renal glucose release of the ablated kidney during conditions of severe hypoglycaemia was significantly diminished compared to that of the non-ablated organ.…”
Section: Introductionmentioning
confidence: 99%